2017
DOI: 10.1016/j.ebiom.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Organization of lncRNA and Circular RNA Regulators Collectively Controlled Cardiac Differentiation in Humans

Abstract: Advances in developmental cardiology have increased our understanding of the early aspects of heart differentiation. However, understanding noncoding RNA (ncRNA) transcription and regulation during this process remains elusive. Here, we constructed transcriptomes for both long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) in four important developmental stages ranging from early embryonic to cardiomyocyte based on high-throughput sequencing datasets, which indicate the high stage-specific expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 68 publications
0
89
0
Order By: Relevance
“…With the development of next-generation sequencing technology, it is realized that the most part of human genome is transcribed to noncoding RNAs [2]. Of these newly discovered RNA regulatory elements, long noncoding RNAs (lncRNAs) have been demonstrated to play critical roles in diverse cellular processes [3][4][5]. LncRNAs can serve as signal mediators, scaffold or molecular decoys to function in epigenetic, transcriptional and posttranscriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing technology, it is realized that the most part of human genome is transcribed to noncoding RNAs [2]. Of these newly discovered RNA regulatory elements, long noncoding RNAs (lncRNAs) have been demonstrated to play critical roles in diverse cellular processes [3][4][5]. LncRNAs can serve as signal mediators, scaffold or molecular decoys to function in epigenetic, transcriptional and posttranscriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics may place circRNA at the forefront of potential candidates for diagnostic and prognostic biomarkers for diseases, and especially since circRNA is present in the plasma (Salgado‐Somoza, Zhang, Vausort, & Devaux, ). circRNAs often exhibit cell type, tissue, and developmental stage‐specific expression in organisms (Jakobi, Czaja‐Hasse, Reinhardt, & Dieterich, ; Li et al, ; Memczak et al, ; Xu et al, ). The expression profiles of circRNA were different at four heart differentiation stages: undifferentiated, mesoderm, cardiac progenitor, and definitive cardiomyocytes (Li et al, ). Werfel et al observed significantly higher overall circRNA expression in rat neonatal hearts compared with adult rat hearts (Werfel et al, ); and remarkable changes in circRNA expression were also observed amongst different stages of induced pluripotent stem cell‐derived cardiomyocytes (Siede et al, ). circRNAs seem to be evolutionarily conserved as evident by their homologous sequences across species (Jeck et al, ).…”
Section: Classification Of Circrnamentioning
confidence: 99%
“…There is increasing evidence to indicate the functional involvement of these regulatory miRNAs, vault complex-associated RNAs (vtRNAs) and lncRNAs in influenza virus replication (21,22). For example, some studies have demonstrated that ncRNAs can regulate the activation of pattern recognition receptor (PRR)-associated signaling and transcription factors, as well as the production of interferons (IFNs) and the expression of critical IFN-stimulated genes (ISGs) (23,24). In addition to these ncRNAs, circular RNAs (circRNAs) are a novel type of RNA that, unlike linear RNAs, form a covalently closed continuous loop, and are highly represented in the eukaryotic transcriptome (25,26).…”
Section: Introductionmentioning
confidence: 99%